If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3x = 3x + 2 Reorder the terms: 8 + -3x = 2 + 3x Solving 8 + -3x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + -3x + -3x = 2 + 3x + -3x Combine like terms: -3x + -3x = -6x 8 + -6x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + -6x = 2 + 0 8 + -6x = 2 Add '-8' to each side of the equation. 8 + -8 + -6x = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = 2 + -8 -6x = 2 + -8 Combine like terms: 2 + -8 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| 66=9x-13-8x+29 | | x/8+6=-12 | | 23-(-11)= | | w+(-9)=-4 | | 3x-15=3x | | 8x=6x-14 | | 2x-3=32 | | 15=5x-3(x+7) | | 4x-6=10x | | 21+29x=42+22x | | 81k^2-49=0 | | -[4z-(12z+6)]=6+(7z+7) | | 8-2a=-12 | | 11=7(x-3)+21 | | 0.4c+4+-5c=-9 | | 11= | | 9x-13-8x=29 | | 36+4r=-4(r+7) | | -10x=260 | | 7(x+7)=2x+57 | | 138-4=2l+4-4 | | 6z+z=6z+9 | | 3x+6=4w | | .2x=7-.6x | | 1-5x=-4-4x | | -11x+9-4x=2 | | y/4=15/6 | | 7s-5-7s+9= | | 10.9x+15.56=-9.1x+13.86 | | m+3-2=7 | | 10.9x+15.56=9.1x+13.86 | | 4x-22=3x+17 |